The Evaluation of Aid Projects and Programmes - Cracknell, Basil E.; Great Britain (London: Overseas Development Administration, 1984)
This conference provided a forum for the ODA to describe its evaluation programme and some of the approaches being developed. Its objective in evaluation is to enable lessons to be learned from the experience of implementing development projects and programmes; then to be sure these lessons are applied to new decisions and passed on to governments and their advisers in the developing world who can translate this information into ultimate benefits for their populations.
"Based on ... the ODA Conference on Evaluation held in the Institute of Development Studies at the University of Sussex, 7-8 April 1983"--P. viii.
Includes bibliographical references.
ne 21/05/2018
Loans
Keywords: Economic assistance; Technical assistance